No one is born with it: Australasian dental students' perceptions of learning manual dexterity. Issue 1 (6th September 2022) - Sim, May Yee; Tan, Li Feng; Adam, Lee; Loch, Carolina
Abstract: Dentistry requires high manual dexterity, and few studies have investigated the challenges and impact on dental students of attaining manual dexterity skills. This study aimed to investigate dental students' perceptions of manual dexterity, including their awareness of manual dexterity requirements in dentistry, self‐perceptions of manual dexterity competency, and whether manual dexterity should be part of admission to dentistry training. A link to a 12‐item online Qualtrics survey was sent out to students in either their 2nd or 5th year of the Bachelor of Dental Surgery (BDS) degree at the University of Otago, New Zealand. The anonymous survey collected basic demographic data and included closed and open‐ended questions about manual dexterity. Descriptive statistics were calculated for quantitative variables and a general inductive approach was used to analyze free‐text responses. Those were later grouped into a theoretical domain framework. The overall response rate was 53%. All participants acknowledged the importance of manual dexterity in dentistry. Most participants thought that manual dexterity can be improved with practice and that including a manual dexterity test in the admission criteria may cause unnecessary stress for students. Striving to achieve manual dexterity impacted participants' performance in the BDS course. However, most participants viewed it as a challenge that can be overcome with practice and improvement, and that current BDS admission requirements are sufficient.